Caracterização química da matéria orgânica, propriedades físicas do solo e produtividade de milho de segunda safra consorciado com plantas de cobertura e soja em sucessão - Mottin, Marcos Cesar (2019)
The objective of the present work was to evaluate the influence of maize crop of second crop intercropped with soil cover plants on soil quality from humic fraction fractions of soil organic matter and soil organic carbon content and; to evaluate the influence of maize crop second crop intercropping with soil cover plants on biomass productivity, soil physical properties and productivity of the soybean and second succession corn crop system. Cultivation of the second crop maize crop was carried out in the agricultural year of 2016 and 2017, and the soybean crop of the 2016 - 2017 crop was also cultivated. The experimental design was a randomized block design (DBC) with four repetitions. The plots were constituted by corn cultivation in monoculture and with a consortium with different soil cover plants. The species of plants used in the consortium were: two from the family Poaceae (Urochloa ruziziensis and Avena strigosa S.) and two from the family Fabaceae (Cajanus cajan and Crotalaria spectabilis). The cultivation of soybeans grown in succession on the different straw. The factors evaluated in this work were: Fractions of the humic substances of the organic matter of the soil; Total organic carbon content of soil; Dry mass yield; Volume of macropores, micropores, total porosity; soil density; soil penetration resistance; Productivity of the second soybean-corn crop system and the productivity of the soybean crop. In the first year the intercropping system of corn intercropped with soil cover plants increased the total organic carbon content and its fractions. Corn intercropping with soil cover plants of the family Poaceae and Fabaceae increased the total organic carbon contents at different depths; in the Poaceae there was an increase in the total organic carbon contents in the depth of 0 - 0.20 m, while in the Fabaceae there was an increase in the depth of 0.20 - 0.40 m. Cover plants have demonstrated great potential in promoting soil quality in the no-tillage system. After two corn intercropping with cover crops there was an improvement in the soil organic matter quality, observed in the percentage of humin that represents the greater part of the humified carbon. The second maize crop consortium system with soil cover plants did not promote the increase of dry mass on the soil, nor did it influence soil resistance to root penetration. The cultivation of corn intercropped with cover crops of the Poaceae family, especially the brachiaria, is more efficient for increasing the dry mass when compared to the Fabaceae family. They are also more efficient in promoting improvements in macroporosity and reduction in soil density at depths of 0 - 0.10 m. And within the Poaceae family, brachiaria are more efficient than black oats. In general, maize intercropping with soil cover plants promoted better physical soil quality in the depth of 0 - 0.10 m. Although, the maize consortium with cover crops has improved the physical quality of the soil; it reduced the system's grain yield (corn and soybean) by 5% in the 2016 and 2017 crop years. The cultivation of soybean cultivation on corn straw intercropped with soil cover plants promoted an increase in productivity of 0.19 Mg ha-1. Being the highest productivity of the family Fabaceae, and within this the soybean in succession to the dwarf pigeon bean promoted a 5% increase in productivity.